2017
DOI: 10.1093/cercor/bhx101
|View full text |Cite
|
Sign up to set email alerts
|

Secretagogin is Expressed by Developing Neocortical GABAergic Neurons in Humans but not Mice and Increases Neurite Arbor Size and Complexity

Abstract: The neocortex of primates, including humans, contains more abundant and diverse inhibitory neurons compared with rodents, but the molecular foundations of these observations are unknown. Through integrative gene coexpression analysis, we determined a consensus transcriptional profile of GABAergic neurons in mid-gestation human neocortex. By comparing this profile to genes expressed in GABAergic neurons purified from neonatal mouse neocortex, we identified conserved and distinct aspects of gene expression in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 79 publications
(110 reference statements)
6
40
0
Order By: Relevance
“…Young interneurons in the putative ferret postnatal streams express several markers associated with an origin in the ventral pallium (Ma et al, ; Raju et al, ). We found they express Sp8 and SCGN to varying degrees, two markers of interneurons shown to be expressed in cells originating in the caudal ganglionic eminence (CGE) and lateral ganglionic eminence (LGE).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Young interneurons in the putative ferret postnatal streams express several markers associated with an origin in the ventral pallium (Ma et al, ; Raju et al, ). We found they express Sp8 and SCGN to varying degrees, two markers of interneurons shown to be expressed in cells originating in the caudal ganglionic eminence (CGE) and lateral ganglionic eminence (LGE).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, secretagogin had been observed in neurons in multiple structures in the rodent brain, such as the RMS, olfactory bulb, hypothalamus, dentate gyrus and amygdala, but not cortex (Kosaka & Kosaka, ; Mulder et al, , ; Romanov et al, ). Recently, it was shown that human cortex contains SCGN+ interneurons, and forced expression in mice increases neurite outgrowth (Raju et al, ). The discovery that the ferret also contains SCGN+ interneurons, both in the white matter and cortex, that persist into adulthood, implies that SCGN+ interneurons may represent a change in cortical development found only in gyrencephalic brains whose function and circuit contributions can be further studied using ferret as a model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences have been interpreted by Mulder et al as uncovering phylogenetic differences in SCGN expression. More recently, it has also been reported that SCGN is expressed by developing neocortical GABAergic neurons in humans but not in mice (Raju, Spatazza, Stanco, Sorrells, & Kelley, ). In the human brain, SCGN immunostaining has been described in both cerebellar basket and stellate cells and in neurons of temporal, frontal, hippocampal, and hypothalamic regions (Gartner et al, ).…”
Section: Introductionmentioning
confidence: 99%